RARE-36. BORTEZOMIB WOKE UP A PATIENT WITH ANTI-NMDA RECEPTOR ENCEPHALITIS REFRACTORY TO STANDARD THERAPY AND LONG TERM FOLLOW-UP. (11th November 2019) - Xiao-Tang, Kong; Groysman, Leonid; Dastur, Cyrus; Fu, Beverly; Bota, Daniela
Abstract: OBJECTIVE: To report a case with refractory NMDA encephalitis in comatose for 18 months, who was treated successfully with bortezomib. BACKGROUND: Anti-NMDA encephalitis is a rare autoimmune encephalitis. Standard therapy include corticosteroid, IVIG or plasma exchange, cyclophosphamide, rituximab, and tumor removal. Refractory cases are very severe and often stay in ICU on ventilation for several months to years. Bortezomib for the treatment of refractory anti-NMDA receptor encephalitis was reported. We have applied the treatment to our refractory case and successfully woke up the patient. And we have followed up the patient for 3 years. METHODS: Case report. RESULTS: A 40 yo male was diagnosed as anti-NMDA encephalitis. Standard therapy was applied. After stabilization, the patient was eventually discharged to ICU at a long term care subacute hospital. The patient was brought back for more Rituxan or steroid or IVIG therapy. The condition had not improved at all. Eighteen months in comatose, the patient had worsening NMDA titer in CSF to 1:640. Decision was made to start bortezumib as reported with modification: 1.3 mg/m2 bortezomib were administered on days 1, 8, 11 and 14 and allowed two weeks off therapy. After first cycle, the patent started to talk first word "hurt." After 6 cycles, the patient sat up and started riding bicycles for physical therapy. The NMDA titer in CSF was reduced to 1:40 at the end of 6 cycles. One year later, the patent stood up and ambulated with a walker. One and half year later, the patient walks without assistance and his speech and cognition have significantly improved with good communication with family members and staff. CONCLUSIONS: Proteasome inhibitor bortezomib might be considered to be the third line therapy as early as possible if the first line and second line are ineffective to treat anti-NMDA receptor encephalitis.